Discussion on standardization of Traditional Chinese Medicine nursing appropriate Technology based on Traditional Chinese Medicine nursing inheritance (基于中医护理传承构建标准化中医护理适宜技术) - LIU Hongxin (刘红鑫); GUO Hailing (郭海玲); TIAN Runxi (田润溪); WANG Fang (王芳); GAO Ning (高宁); ZHENG Liping (郑莉萍); LI Yufeng (李玉凤); YU Liying (于丽英) (中西医结合护理)
The appropriate technology of Traditional Chinese Medicine (TCM) nursing is an important part of TCM. Based on the deeply understanding Professor Guo Hailing 's academic thought of " inherit traditional Chinese medicine nursing with love, evidence-based innovation and development of teaching", evidence-based nursing methods was used to standardize TCM nursing appropriate technology and promote it to clinical practice. It can help to provide basis for clinical optimization of TCM nursing appropriate technology and provide efficient nursing mode for patients. At the same time, to cultivate high-level TCM nursing talents with evidence-based thinking and nursing practice ability. (中医护理适宜技术是中医学的一个重要组成部分, 深入领会郭海玲教授“仁爱传承中医护理, 教学循证创新发展”的学术思想, 培养具备循证思维和护理实践能力的高层次中医护理人才, 运用循证护理方法构建中医护理适宜技术的标准化, 提升中医护理水平, 为临床优化中医护理适宜技术提供依据, 为患者提供高效的护理模式。)